2020
DOI: 10.14712/18047106.1548
|View full text |Cite
|
Sign up to set email alerts
|

Investigating subject matter knowledge and pedagogical content knowledge in mathematics with the Concept Cartoons method

Abstract: The article focuses on an educational tool called Concept Cartoons and its possible use in professional preparation of future primary school teachers. In particular, it presents the method of how Concept Cartoons can be employed as a tool for diagnosing subject matter knowledge and pedagogical content knowledge in mathematics. The first part of the contribution introduces the concept of teachers' knowledge that is used in the article, and the Concept Cartoon tool. It describes the original Concept Cartoons met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Each Concept Cartoon has a form of a picture with a school or out-of-school everyday situation related to a given curricular content and several children discussing the situation through a bubble dialogue. Our previous research showed how Concept Cartoons might be used as a tool for diagnosing various types of teacher knowledge (e.g., Samková, 2019). In this study, we employ three Concept Cartoons related to the topic of general statements, one located in arithmetic, one in biology and one in geometry.…”
Section: Diagnostic Instrument -Common Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each Concept Cartoon has a form of a picture with a school or out-of-school everyday situation related to a given curricular content and several children discussing the situation through a bubble dialogue. Our previous research showed how Concept Cartoons might be used as a tool for diagnosing various types of teacher knowledge (e.g., Samková, 2019). In this study, we employ three Concept Cartoons related to the topic of general statements, one located in arithmetic, one in biology and one in geometry.…”
Section: Diagnostic Instrument -Common Aspectsmentioning
confidence: 99%
“…In recent years, we have been analysing an educational tool called Concept Cartoons (Keogh and Naylor, 1999) and its possible use in the professional preparation of future teachers, especially in investigating various aspects of teacher knowledge in mathematics. We focused on Concept Cartoons as a tool for assessing reasoning on arithmetic topics (e.g., Samková and Tichá, 2017), in qualitative as well as mixed research designs (Samková, 2019). To systematically map the terrain, we naturally proceeded to a question whether and how it is possible to use Concept Cartoons to assess reasoning about mathematical statements.…”
Section: Introductionmentioning
confidence: 99%
“…When the related literature is examined, it is seen that concept cartoons are frequently used in other fields of mathematics education. Samkova (2020) examined the mathematical pedagogical content knowledge of classroom teachers using concept cartoons. Yilmaz (2020) stated that education supported by concept cartoons had positive effects on the success of fourth-grade students in the "earth crust" unit.…”
Section: Introductionmentioning
confidence: 99%